Conceptual Design Of Reverse And Jaw Detector Jig - Mohamed Noor, Ahamad Zaki (2015)
Essentra Component is a company located in Ipoh, Perak which produce seals. There are two types of seal available in the company which are metal and plastic seals. The production plant still employs fully manual operation for most of the production line, but some operations are semi – automated. Due to manual assembly, human operator tends to get fatigue for doing repetitive task in one long shift. When this occurs, minor error such as misplace or wrong orientation of jaw will occur. Customers complain that the seal, especially those plastic seals are not functioning well. The quality problem sometimes not purposely done by the operator during placing the jaw in reverse orientation and moreover the jaw sometimes can be missing during transportation of work – in – progress to the ultrasonic welding station. This jig is designed to have the ability to detect reverse jaw or missing jaw and so that the finish product which has the quality problem will be prevented from being shipped to customers. The jig must also have a flexibility to be used for other plastic seal product. Under chapter 2, jig definition is known, the method of designing, suitable type of sensors, sample jig which used and research on decision making tool. As for methodology, a project schedules being developed in the form of Gantt chart to have time restriction in producing the concept design of reverse and missing jaw jig. Each and every stage was explained in detail in the methodology chapter. In result and discussion, House of Quality (HOQ) have been used to determine the highest weightage criteria. The important criteria which will be carried forward to Analytical Hierarchy Process (AHP) are 15.9% on flexibility and ease of maintenance, 15.4% on both ease of use and longevity of jig usage, lastly 15.2% for accuracy checking. The result obtain after AHP computation are Design 1 with 20.7%, Design 2 with 13.7%, Design 3 with 22%, Design 4 with 27.1% and Design 5 with 16.5%. Design 4 is selected due to the highest weightage after computation. Last chapter consists of a conclusion that has been drawn out from overall research project where final design is justified its properties and why should it be fabricate. Some suggestions are mentioned for future work in order to obtain better reading to make a better judgement.